The Interface and User Experience Design of the Mobile Application “TUNEMATE” for Discovering a Music Companion and Attending Concerts - Yudistira Putra; Pratama Bayu Widagdo (Gorga : Jurnal Seni Rupa, 2025)
Finding friends with similar musical interests provides benefits for expanding friendship relationships. In addition, music friends also have the opportunity to become friends and watch concerts together. The difficulties faced in finding music friends and concert events require a solution in the form of designing the UI/UX of an application called Tunemate. This research applies a design thinking approach to create products that are oriented to user needs. The data collection method includes observation of music streaming applications, social media, and online ticket purchase platforms. For online questionnaires and user interviews, there are criteria from music streaming fans and concert activists. The data analysis method is by applying a qualitative method whose process follows each stage of the design thinking approach. The final result of the research created a prototype of the UI/UX design that was tested through Maze. The usability score obtained in Maze from the testing stage shows a score of 82 points.  The design of the Tunemate application is suitable for users who want to experience a new way of using music streaming applications combined with social media and concert events. Overall, the appearance and features received positive feedback from the testers, who were very enthusiastic about the prototype. Thus, the design of the UI/UX of the Tunemate application has met the needs of users and is a one-stop solution to finding music friends, searching, as well as buying concert tickets and merchandise.